PENGARUH KEBIJAKAN MONETER TERHAP KINERJA LEMBAGA KEUANGAN - Arini Nurfaizah; Umar Faruk; Moh. Norkholis; Ahmarul Fajar (PT. Hasba Edukasi Mandiri, 2026)
Monetary policy implemented by Bank Indonesia has a fundamental or significant impact on banking performance and economic growth in Indonesia. The primary objective of this policy is to achieve exchange rate stability, low inflation, and sustainable economic growth. The positive impact of monetary policy on Indonesia's economic growth is evident through financial system stability, stable interest rates, and maintained exchange rates. In addition, this monetary policy also affects banking performance through bank profitability, credit distribution, and bank asset quality. Economic growth is influenced by monetary policy through investment, consumption, and trade, where low interest rates and stable exchange rates play a central role in driving economic growth both in the long and short term.